Recommendations for CSF AD biomarkers in the diagnostic evaluation of dementia. Issue 3 (27th October 2016) - Simonsen, Anja Hviid; Herukka, Sanna-Kaisa; Andreasen, Niels; Baldeiras, Ines; Bjerke, Maria; Blennow, Kaj; Engelborghs, Sebastiaan; Frisoni, Giovanni B.; Gabryelewicz, Tomasz; Galluzzi, Samantha; Handels, Ron; Kramberger, Milica G.; et al.
Abstract: This article presents recommendations, based on the Grading of Recommendations, Assessment, Development, and Evaluation method, for the clinical application of cerebrospinal fluid (CSF) amyloid‐β1–42, tau, and phosphorylated tau in the diagnostic evaluation of patients with dementia. The recommendations were developed by a multidisciplinary working group based on the available evidence and consensus from focused discussions for (i) identification of Alzheimer's disease (AD) as the cause of dementia, (ii) prediction of rate of decline, (iii) cost‐effectiveness, and (iv) interpretation of results. The working group found sufficient evidence to support a recommendation to use CSF AD biomarkers as a supplement to clinical evaluation, particularly in uncertain and atypical cases, to identify or exclude AD as the cause of dementia. Because of insufficient evidence, it was uncertain whether CSF AD biomarkers outperform imaging biomarkers. Operational recommendations for the interpretation of ambiguous CSF biomarker results were also provided.